(untitled) (Przegląd Religioznawczy – The Religious Studies Review, 2023)
The passages of the First and Second Epistles of Peter are the subject of analysis in this article: those in which the terms prophētēs and prophēteia appear; those that can be considered prophetic oracles; and those that contain quotations from prophetic books. When read in the key of content related to the phenomenon of prophetism, these writings demonstrate the existence of at least three aspects of this phenomenon. Firstly, the author points to the fact that the prophecies of the Old Testament were fulfilled in the life of Jesus and fulfilled in the mission of the young Church. Secondly, both writings contain numerous direct quotations taken from the prophetic books. Thirdly, and finally, the author of the letters himself proves to be a New Testament prophet, foretelling and interpreting the events of salvation history.